2019
DOI: 10.18203/2320-1770.ijrcog20196049
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on maternal and perinatal outcome of placenta previa-risk factors, morbidity and mortality in JNIMS, Imphal, India

Abstract: Background: The observational study to analyse the maternal and perinatal outcome in pregnancies complicated with placental previa evaluating the potential risk factor, associated with morbidity and mortality.Methods: The study was a prospective longitudinal comprising of all the pregnant women after 28 week of gestation irrespective of gravid and parity that attended or admitted in the department of obstetrics and gynaecology, JNIMS, diagnosed as having placental previa by transabdominal ultrasonography and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Maunica et al [4] Shruthi et al [9] Santosh et al [10] Haripriya et al [11] Meenakshi et al [2] Present Study Majority of the women were multigravida (79%) concluding that there is increased risk of placenta previa with increasing parity. Major risk factor was previous LSCS in 34.3% women also concluded that previous scar act as nest for the implantation of the placenta in the lower uterine segment.…”
Section: Variables Maiti Et Al[3]mentioning
confidence: 91%
See 1 more Smart Citation
“…Maunica et al [4] Shruthi et al [9] Santosh et al [10] Haripriya et al [11] Meenakshi et al [2] Present Study Majority of the women were multigravida (79%) concluding that there is increased risk of placenta previa with increasing parity. Major risk factor was previous LSCS in 34.3% women also concluded that previous scar act as nest for the implantation of the placenta in the lower uterine segment.…”
Section: Variables Maiti Et Al[3]mentioning
confidence: 91%
“…Maiti et al [3] Maunica et al [4] Shruthi et al [9] Santosh et al [10] Haripriya et al [11] Meenakshi et al [2] Present Study…”
Section: Variablesmentioning
confidence: 99%